THE RELATIONSHIP BETWEEN RELIGIOSITY AND PEER SOCIAL SUPPORT WITH PSYCHOLOGICAL WELL-BEING AMONG FEMALE STUDENTS AT DEMAK STATE HIGH SCHOOL 1 - Astiko, Anggraheni Putri; Munawaroh, Eem (LP2M IAI Al-Khairat Pamekasan, 2026)
Adolescence is a crucial period marked by complex changes in physical, cognitive, and emotional aspects. Psychological well-being is an important foundation for adolescents in facing academic and social challenges. This study aims to analyze the relationship between religiosity and peer social support with psychological well-being in female students at SMA Negeri 1 Demak. The research design employs a quantitative correlational approach using total sampling, involving 240 female students in grade XI at SMA Negeri 1 Demak. The research instruments include the Centrality of Religiosity Scale, the Multidimensional Scale of Perceived Social Support, and the Psychological Well-being Short Scale, which have been validated through Confirmatory Factor Analysis. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25. The results of the study indicate that there is a relationship between religiosity and peer social support with psychological well-being among female students at SMA Negeri 1 Demak, with a significance value of 0.000 (p < 0.05). Both variables contribute 30.9% to the variance in students' psychological well-being. This study concludes that religiosity and peer social support are proven to be significant protective factors in enhancing psychological well-being among adolescent girls. Further research is recommended to be conducted in several schools to better generalize the findings.